ANALISIS LEVEL BERPIKIR SISWA BERDASARKAN TAKSONOMI SOLO DALAM MENYELESAIKAN SOAL CERITA SPLDV DITINJAU DARI TIPE KEPRIBADIAN FLORENCE LITTAUER (KadikmA, 2018)
Abstract. This research aims to describe the level thinking of students based on SOLO taxonomy in completing SPLDV story questions in terms of Florence Littauer's personality type. Data was obtained based on the results of questionnaires, tests and interviews. The subjects of this study were class VIII D SMP Negeri 2 Jember. The results showed that students with a sanguinis personality type were 30% at an unistructural level, 20% at a multistructural level and 50% at a relational level. Students with choleric personality types each 33.33% were at the level of multistructural, relational and extended abstract. Students with a melancholic personality type of 25% are at a multistructural level, 55% at a relational level and 20% at an extended abstract level. Students with a phlegmatic personality type of 15% are on an unistructural level, 35% on a multistructural level, 35% on a relational level and 15% on an extended abstract level. Keywords: SOLO Taxonomy, Personality Type, Thinking Level, SPLDV.